2024
DOI: 10.1021/jacs.3c12240
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomics Identifies State-Dependent and Proteoform-Selective Caspase-2 Inhibitors

José O. Castellón,
Samuel Ofori,
Nikolas R. Burton
et al.

Abstract: Caspases are a highly conserved family of cysteine-aspartyl proteases known for their essential roles in regulating apoptosis, inflammation, cell differentiation, and proliferation. Complementary to genetic approaches, smallmolecule probes have emerged as useful tools for modulating caspase activity. However, due to the high sequence and structure homology of all 12 human caspases, achieving selectivity remains a central challenge for caspase-directed small-molecule inhibitor development efforts. Here, using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 118 publications
(215 reference statements)
0
0
0
Order By: Relevance
“…Whether or not a defined small molecule binding site is present in RTN4 is still unclear, as the protein remains structurally unresolved in the PDB and is highly disordered in the AlphaFold model (Figure S18; ID: AF-Q9NQC3-F1). Notably, C1101 exhibits hyperreactivity towards the cysteinereactive probe iodoacetamide alkyne (IAA) [84][85][86] , which is suggestive that cysteine reactive may be a central driver of RTN4 labeling by our asciminib probes.…”
Section: High Accuracy Quantification Of Relative Binding Site Engage...mentioning
confidence: 95%
See 1 more Smart Citation
“…Whether or not a defined small molecule binding site is present in RTN4 is still unclear, as the protein remains structurally unresolved in the PDB and is highly disordered in the AlphaFold model (Figure S18; ID: AF-Q9NQC3-F1). Notably, C1101 exhibits hyperreactivity towards the cysteinereactive probe iodoacetamide alkyne (IAA) [84][85][86] , which is suggestive that cysteine reactive may be a central driver of RTN4 labeling by our asciminib probes.…”
Section: High Accuracy Quantification Of Relative Binding Site Engage...mentioning
confidence: 95%
“…We also observed that STING (TMEM173), an important regulator of innate immunity which elicits anti-tumor immune responses and a target of a number of chemical probe and drug development campaigns 82,83 , was also enriched and competed only in K562 cells (Figure 5C). Given our interest in mapping labeling sites we were also intrigued to observe reticulon-4 (RTN4) as a target of asciminib, due to the presence of a hyperreactive cysteine residue in this key regulator of endoplasmic reticulum structure (Figure 5A-C) [84][85][86][87][88] . Strikingly absent from the proteins significantly enriched by 5b was the bona fide target of asciminib ABL1 kinase-of note, several peptides from BCR were detected as modestly enriched, albeit below the threshold of significance (Figure 5D).…”
Section: Synthesis Of Dasatinib and Asciminib See-cite Probesmentioning
confidence: 99%